The Responsible Entrepreneur : Four Game-Changing Archetypes for Founders, Leaders, and Impact Investors. - Sanford, Carol (Wiley, 2014)
""Individuals, acting on deeply held beliefs and passion, are boldly imagining and bringing into existence a different world ... Whether you're a business entrepreneur, a social entrepreneur, an investment entrepreneur, or an academic, artistic, or civil servant entrepreneur, devour this important and wise book.""--The Foreword by John Fullerton Responsible entrepreneurs are a special breed, seeking to transform industries and even society itself. They challenge and refine cultural assumptions, laws, regulations, and even the processes of governance. This requires them to do and think.